2020
DOI: 10.3390/rs12244103
|View full text |Cite
|
Sign up to set email alerts
|

Mapping an Urban Boundary Based on Multi-Temporal Sentinel-2 and POI Data: A Case Study of Zhengzhou City

Abstract: Accurately identifying and delineating urban boundaries are the premise for and foundation of the control of disorderly urban sprawl, which is helpful for us to accurately grasp the scale and form of cities, optimize the internal spatial structure and pattern of cities, and guide the expansion of urban spaces in the future. At present, the concept and delineation of urban boundaries do not follow a unified method or standard. However, many scholars have made use of multi-source remote sensing images of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The remote sensing data sources used include MODIS [13,14], the Landsat series [15][16][17][18], and DMSP/OLS nighttime light data [19][20][21][22], but the spatial resolution of these remote sensing products is relatively low. High-resolution remote sensing data sources include QuickBird, IKONOS, and Gaofen2 [23][24][25]; these products are very expensive, and Sentinel-2, which is free and has high resolution, has therefore become the data source of choice for many studies [26]. By processing remote-sensing images and extracting remote-sensing information and features, the boundaries of built-up urban areas can be better extracted [10].…”
Section: Introductionmentioning
confidence: 99%
“…The remote sensing data sources used include MODIS [13,14], the Landsat series [15][16][17][18], and DMSP/OLS nighttime light data [19][20][21][22], but the spatial resolution of these remote sensing products is relatively low. High-resolution remote sensing data sources include QuickBird, IKONOS, and Gaofen2 [23][24][25]; these products are very expensive, and Sentinel-2, which is free and has high resolution, has therefore become the data source of choice for many studies [26]. By processing remote-sensing images and extracting remote-sensing information and features, the boundaries of built-up urban areas can be better extracted [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that, when multitemporal remote-sensing image spectral features are used, the classification effect is much better than with single-temporal remotesensing images [7]. Therefore, in this paper, remote-sensing images for four time periods (months) in Zhengzhou City in 2018 were selected, thus extracting a set of high-dimensional spatial and temporal features.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Land use has been an important research component for global ecological changes and sustainable social development [2][3][4][5]. As a major carrier of basic human life and daily activities, land merits accurate and timely understanding of urban land-use information, which is extremely important for tapping the inherent development potential of cities, improving urban spatial governance, and ensuring highquality urban development [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Zong et al 25 focused on the data sources and combined POI data, remote sensing images and road network datasets to achieve fine-grained classification of urban functional zones. It can be argued that the utilization of POI data in urban functional zone research yields significant advantages, particularly in improving accuracy 26,27 and reducing costs 28,29 . However, a notable shift towards understanding urban functional zones based on POI data in cities has been noticed [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%